Analysis of Genetic Diversity Indonesian Ducks Using Microsatellite Marker - Maharani, Dyah; Hariyono, Dwi Nur Happy; Cho, Sunghyun; Manjula, Prabuddha; Seo, Dongwon; Choi, Nuri; Sidadolog, Jafendi Hasoloan Purba; Lee, Jun Heon (2018)
Conservation of genetic diversity plays an important role in sustaining local breeds. A number of Indonesian local duck breeds, namely Bayang, Pegagan, Pitalah (Sumatran Ducks), Magelang, Mojosari, Rambon, and Turi (Javanase Ducks) are included as local assets and play an important role in socio-economic. A total of 206 ducks corresponding to Sumatran (SM) and Javanese (JW) duck populations was estimated using 22 duck microsatellite markers. Within the twenty-two polymorphic loci, number of alleles per locus (Na), polymorphism information content (PIC), observed heterozygosity (Ho), expected heterozygosity (He), Hardy-Weinberg equilibrium (HWE) test and Wright’s F-statistics were determined by Cervus and GenAlEx software. As a results, three to 22 alleles per locus were found across all the populations. The PIC, Ho and He across all populations ranged from 0.087 (APH24) to 0.907 (CAUD040), from 0.029 (APH24) to 0.863 (CAUD048) and from 0.090 (APH24) to 0.916 (CAUD0448), respectively. Nine loci were detected under Hardy-weinberg equilibrium (P<0.01). The JW duck population were indicated to have higher genetic variation (Na=6.32; Ne=3.15; Ho=0.465; He=0.578) compared to SM duck. The mean fixation coefficient of subpopulation within the total population which indicated approximately 39% of the genetic variation was due to population differences, and 61% was caused by differences of among individuals. The moderate magnitude of genetic diversity observed within the investigated duck populations suggests that these populations are quite rich reservoirs of genetic diversity that should be preserved.